Label-free analysis of biomolecular interactions using SPR imaging - Voula Kodoyianni (BioTechniques)
Surface plasmon resonance (SPR) is a label-free detection method by which molecular interactions may be analyzed on a surface. Binding data are collected in real time, allowing the determination of interaction kinetics. SPR imaging (SPRi), the focus of this review, improves upon the efficiency of SPR by facilitating analysis of multiple interactions simultaneously. Here we summarize the principles of SPRi, provide examples of how SPRi arrays can be fabricated, and illustrate the utility of SPRi through example applications from the fields of proteomics, genomics and bioengineering.